Eco-Friendly Medical Devices: Bridging the Gap between Environmental Sustainability and Healthcare - Khalaf, Doaa Khalaf Kandouh; Karim, Farhad Fryad Adil; Omer, Younis Dler Salah; Faraj, Ayaat Basim Ali; Mohammed, Mohammed Munir shareef (American Journal of Biodiversity, 2025)
The world is experiencing an aging population and chronic diseases deeply affecting the fundamental structure of healthcare systems. National and international organizations together with design communities are currently addressing new approaches to foster realistic tools, such as innovative, eco-friendly solutions. Healthcare design has recently been included into the Sustainable Design field to pursue strategies aimed at reducing energy consumption and hazardous substances in products .This paper discusses brief guidelines to develop a new sector of eco-friendly medical devices, with the aim to bridge the gap between environmental sustainability and healthcare by combining information and perspectives from diverse sectors and individuals, amongst corporate managers, healthcare employees, patients, students and scholars of diverse disciplines. The integration of different competences and roles is necessary to enhance corporate responsibility and to disclose socio-ecological exceedings due to healthcare products life cycle. Experiencing hospitals and specialistic universities, this discussion further broadens the debate on healthcare as a multi-layered open system connected to diverse and changing context. New research will be addressed to Analytical Design methods, focusing on the study of energy requirements and ethic consequences of medical devices related to the therapeutic phases. Finally, the role of R&D and the ongoing Industrial Design project will be discussed, aimed at the restitution of a sustainable, interdisciplinary modular system.